Genetic diversity of ghost crabs from Sematan, Satang Island and Bako National Park using Pcr-Rapd approach - Junirah, Jamil (Universiti Malaysia Sarawak (UNIMAS), 2012)
Homed ghost crab Ocypode ceratophthalmus can be easily found on sandy beaches around Sarawak and other Indo-Pacific countries. They act as bioindicator as well as a very important member of beach food web. Although homed ghost crab are abundant at sandy beaches of Sarawak, limited studies had been carried out on this species. The aim of this study is to document the PCR-RAPD profile of ghost crabs sampled from Sematan, Satang Islan and Bako National Park because of limited information on homedgho t crabs inhabiting Sarawak sandy beaches. A total of 30 samples were collected from Sematan, Satang Island and Bako National Park and they are identified as Ocypode ceratophthalmus and Ocypode sp. Out of 30 samples, 9 samples were subjected to PCR-RAPD analysis. A total of II alleles were successfully detected by using OPA-OI primer and the data obtained shows 90.9% of polymorphism and 9.09% monomorphism between the samples taken from three sampling area.